Grammatical Gaps in Student Translations: Analyzing English-Indonesian Translation in Academic Projects - Veni Roza; Melani, Melyann; Zulfahmi, Muhammad Riko Yohansyah (The Institute of Research and Community Service (LPPM) - Universitas Lancang Kuning, 2024)
Translating messages across languages while maintaining grammatical equivalence presents significant challenges, often resulting in deviations. These deviations stem from differences in grammatical structures between the source and target languages. This qualitative research study aimed to analyze the translation outputs of students enrolled in an English-Indonesian translation course, with a primary focus on grammatical equivalence indicators. The study encompassed 70 students across two parallel classes, resulting in a total of 70 documents available for analysis. The data were collected from the students' responses to a project involving news texts, specifically a news article from The Jakarta Post. The analysis employed Corder and James' Error Analysis (1998) methodology, encompassing error identification, classification, and specification based on grammatical equivalence indicators. The findings revealed that students frequently made errors in various grammatical aspects, including tense, aspect, number, voice, and person, with the exception of gender. Additionally, the study identified specific challenges related to the misplacement of English modifiers within noun phrases, leading to inaccuracies in their translations. These results underscore the importance of balancing theory and practical application in English language teaching, specifically in the context of translation. Emphasizing grammatical equivalence in both English and Indonesian is essential to enable students to produce accurate and idiomatic translations. This study not only sheds light on the challenges faced by students when translating from English to Indonesian but also offers valuable insights for enhancing translation education.